Dynamic modeling in environmental planning: A global synthesis of research addressing urban air quality - Santoso, Dian Hudawan; Santosa, Sri Juari; Sekaranom, Andung Bayu (OPSI, 2025)
This research constitutes bibliometric analysis about the utilization of System Dynamics (SD) in mitigating air pollution. This project aims to investigate the use of system dynamics models in simulating and assessing urban transportation regulations, industrial emissions, and the incorporation of cleaner technology. The applied methodology encompasses a synthesis of current studies and the execution of bibliometric analysis to discern trends, prominent academics, and the most impactful papers in this domain. An exhaustive analysis of the current literature uncovered several significant findings. Investments in public transportation, the introduction of fuel taxes, and the advancement and deployment of sophisticated car technologies are recognized as essential solutions for mitigating air pollution. Case studies from places such Greater Cairo, Kuwait, Tehran, and Mexico City illustrate the efficacy of SD in forecasting long-term environmental consequences and facilitating adaptive policy.This research primarily contributes to the visualisation of the intellectual framework of the research domain, the identification of keyword clusters, and the elucidation of links between topics that may have previously lacked obvious mapping.  This research addresses a methodological deficiency by clearly illustrating how the combination of quantitative bibliometric analysis and systematic review can enhance comprehension of the developmental dynamics within a scientific subject.